KESULITAN BELAJAR SISWA PADA PROSES PEMBUATAN BUSANA KERJA WANITA KELAS XI JURUSAN TATA BUSANA SMK NEGERI 6 PADANG - Adriani, Willi; Zahri, Wildati; Yasnidawati, Yasnidawati (Journal of Home Economics and Tourism, 2013)
The problems in this research is the students can’t make the dress design well, the less precise in measuring, the students can’t understand the good pattern form, the students not careful enough in cutting or scissoring the material, and the students not good enough in sewing. The aim of this research is to describe the student learning difficulties in making women working dress which includes designing the dress, making the pattern, and sewing technique.The kind of this research is quantitative descriptive. The population is all XI grade students fashion department of SMK 6 Padang which are 28 persons. The sample is all population. The data processed by using percentage technique.The result shows that there are 46% students have the middle difficulties in designing, 36% students have the middle difficulties in making pattern, 43% students have the the middle difficulties in sewing, generally, 50% students the middle learning difficulties. Hoped the student can increase their learning system in making ladies working clothes so they can the good achiement Kata Kunci : kesulitan belajar, proses pembuatan, busana kerja wanita